STRATEGIES FOR BUILDING THE CHARACTER OF TOLERANT STUDENTS THROUGH THE MANAGEMENT OF ETHNIC DIVERSITY AT THE SALAFIYAH SYAFI'IYAH SITUBONDO ISLAMIC BOARDING SCHOOL - Sulthoniyah, Luluk; Husnann, Riayatul; Hidayat, Rofiq (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
The Salafiyah Syafi'iyah Sukorejo Situbondo Islamic Boarding School is one of the prominent Islamic boarding schools in East Java, which has an education system and alums who can be said to have a tolerant character and are known to be moderate so that they can respect other groups. This research aims to describe and discover the dynamics of the ethnic diversity of Santri, strategies for forming the character of tolerant Santri through managing ethnic diversity, and the implications of forming the character of tolerant Santri through managing ethnic diversity at the Salafiyah Syafi'iyah Islamic Boarding School in Situbondo. The research was carried out using an interpretive or post-positivistic paradigm approach, a qualitative approach. The type of research carried out was a case study using a case study research design. Determining subjects using purposive data analysis techniques through observation, interviews, and documentation. Data analysis uses condensation, data presentation, and conclusion. Data validity uses triangulation of sources and techniques. The results of the research show that the strategy for building the character of tolerant students through managing ethnic diversity at the Situbondo Salafiyah Syafi'iyah Islamic Boarding School is carried out in a structured manner through systematic and disciplined dormitory placement and schedules assisted by IKSASS administrators. The placement of various ethnically diverse dormitories in one dormitory room makes interaction patterns mutually open, and meeting various cultures makes students appreciate differences.